2023
DOI: 10.1145/3589955
|View full text |Cite
|
Sign up to set email alerts
|

Paper Plain : Making Medical Research Papers Approachable to Healthcare Consumers with Natural Language Processing

Abstract: When seeking information not covered in patient-friendly documents, healthcare consumers may turn to the research literature. Reading medical papers, however, can be a challenging experience. To improve access to medical papers, we explore four features enabled by natural language processing: definitions of unfamiliar terms, in-situ plain language section summaries, a collection of key questions that guides readers to answering passages, and plain language summaries of those passages. We embody these features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…This joint variation is reflected in the guidelines for plain language summaries 3 and in the strategies science writers use to communicate with interested publics [7]. At the same time, these two dimensions have real-world constraints: there are situations in which technical words must be used to convey specific meaning, or where there is a desire to understand the majority of the details in the original scientific article, such as a patient reading a medical research paper or lab report [11,76]. In studies 1 and 2, we allow plainness and information content to vary based on the intended audience ( §4 & §5).…”
Section: Language Complexitymentioning
confidence: 99%
See 4 more Smart Citations
“…This joint variation is reflected in the guidelines for plain language summaries 3 and in the strategies science writers use to communicate with interested publics [7]. At the same time, these two dimensions have real-world constraints: there are situations in which technical words must be used to convey specific meaning, or where there is a desire to understand the majority of the details in the original scientific article, such as a patient reading a medical research paper or lab report [11,76]. In studies 1 and 2, we allow plainness and information content to vary based on the intended audience ( §4 & §5).…”
Section: Language Complexitymentioning
confidence: 99%
“…Adapting interfaces to different users has the potential to improve usability [13,87], aesthetic judgements [28,69], and trust [61,68]. Increasingly, language styles, such as community language norms [26], formality [9], and text complexity [11,95] have been the focus of adaptable user interfaces. Work has shown that language styles can impact behavior in online experiments [9], counseling conversations [4], online communities [26], and security interfaces [98].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations